Prevalence and Risk of Metastatic Thyroid Cancers and Management Outcomes: A National Perspective. (23rd June 2020) - Al‐Qurayshi, Zaid; Sullivan, Christopher B.; Pagedar, Nitin; Lee, Grace S.; Tufano, Ralph; Kandil, Emad
Abstract : Objectives: Examine the prevalence and risk of metastasis in thyroid cancers and management outcomes. Study design: Retrospective analysis of the National Cancer Database, 2004–2014. Methods: The study population included adult (≥ 18 years) patients with thyroid cancer. Analysis included multivariate logistic regression and Cox hazard ratio modeling. Results: A total of 152, 979 patients were included. Distant metastasis was reported in 1, 867 (1.22%) patients. The distribution of metastatic cases based on pathology and tumor size were as follows in descending order: papillary thyroid carcinoma (PTC) 1 to 4 cm (30.53%), PTC > 4 cm (19.34%), undifferentiated (UTC) > 4 cm (14.14%), PTC < 1 cm (8.46%), follicular thyroid carcinoma (FTC) > 4 cm (7.28%), FTC 1 to 4 cm (5.52%), medullary thyroid cancer (MTC) ≤ 4 cm (3.96%), MTC > 4 cm (3.91%), UTC ≤ 4 cm (3.32%), Hürthle (HCC ) > 4 cm (2.09%), and HCC 1 to 4 cm (1.45%). Significant predictors of distant metastasis, while controlling for tumor pathology and size, included older age, male gender, non‐White minorities, presence of multiple comorbidities, minimal, gross extrathyroidal extension (ETE), lymphovascular invasion (LVI), and concomitant central and lateral lymph node metastasis (LNM) ( P < .05 each). The risk of distant metastasis in the absence of nodal metastasis, ETE, and LVI was highest for FTC > 4 cm. Conclusion: Although the risk of metastasis in well‐differentiated thyroid carcinoma (WDTC) is low, the prevalence of metastatic thyroid cancer is highest in WDTC population because it is the most common type of thyroid cancer. Certain pathological features, including minimal ETE and central LNM, are associated with a higher prevalence of metastatic disease. Level of Evidence: NA Laryngoscope, 131:237–244, 2021